Changes in Volatile Compounds of Chinese Luzhou‐Flavor Liquor during the Fermentation and Distillation Process. Issue 11 (7th October 2015) - Ding, Xiaofei; Wu, Chongde; Huang, Jun; Zhou, Rongqing
Abstract: The aim of this study was to investigate the dynamic of volatile compounds in the Zaopei during the fermentation and distillation process by headspace solid‐phase microextraction‐gas chromatography mass spectrometry (HS‐SPME‐GCMS). Physicochemical properties analysis of Zaopei (fermented grains [FG], fermented grains mixed with sorghum [FGS], streamed grains [SG], and streamed grains mixed with Daqu [SGD]) showed distinct changes. A total number of 66 volatile compounds in the Zaopei were identified, in which butanoic acid, hexanoic acid, ethyl hexanoate, ethyl lactate, ethyl octanoate, hexyl hexanoate, ethyl hydrocinnamate, ethyl oleate, ethyl hexadecanoate, and ethyl linoleate were considered to be the dominant compounds due to their high concentrations. FG had the highest volatile compounds (112.43 mg/kg), which significantly decreased by 17.05% in the FGS, 67.12% in the SG, and 73.75% in the SGD. Furthermore, about 61.49% of volatile compounds of FGS were evaporated into raw liquor, whereas head, heart, and tail liquor accounted for 29.84%, 39.49%, and 30.67%, respectively. Each volatile class generally presented a decreasing trend, except for furans. Especially, the percentage of esters was 55.51% to 67.41% in the Zaopei, and reached 92.60% to 97.67% in the raw liquor. Principal component analysis based ordination of volatile compounds data segregated FGS and SGD samples. In addition, radar diagrams of the odor activity values suggested that intense flavor of fruit was weakened most from FG to SGD.